Mandatory rules in recent Serbian jurisprudence and contractual practice - Hiber Dragor (Anali Pravnog Fakulteta u Beogradu, 2022)
Freedom of contract and non-mandatory statutory rules are characteristics of the law on contracts. Mandatory provisions are exceptional and their violation leads to the invalidity of contract and other consequences. Freedom of contract assumes that the rules are non-mandatory, while the exception is to be determined. In a number of cases jurisprudence wavered, and the courts tend to defend their position that a rule is mandatory by invoking the unacceptable position that the Statute has not explicitly allowed different contracting. By contrast, Anglo-Saxon legal institutions representations and warranties and put option are often incorporated in international agreements in which Serbia's law is accepted as applicable, especially in agreements on the sale of shares in limited liability companies. In such cases the jurisprudence is not always willing to recognise and apply mandatory provisions of Serbia's law. In the paper the examples of such practice are subject to a critical analysis.